Building urban spaces in terms of the action: the problems - Bertolotti, Riccardo (E|C, 2021)
This paper discuss one of the very features of the urban spaces, namely the inscription of the human action as a privileged viewpoint for its constitution. Three examples are briefly discussed about how spatial articulations value the postulate of action, thus setting up very diversified types of “model readers”. Expecially in the case of the “dissuasive architecture” of the cities, the matter on how the action is conceived and valued is emphasized. In particular, the modal featuring of dissuasive space is not injunctive (namely it has not the possibility of being constitutive of law), but it is only targeted to mere interdictions regarding the modality of “doing”. In the end, some features about the phenomenological construction of the subject (as “action instance”) are briefly discussed, focusing in partiular Agamben and Husserl.